DETERMINATION OF BUSY HOUR IN MOBILE COMMUNICATION IN NIGERIA (Global Journals of Research in Engineering, 2011)
This paper is focused on determination of busy hour in Mobile Communication in Nigeria, using Lagos as a case study. Busy hour, it is a given period within a day that have the highest traffic intensity. The traffic intensity values obtained within the busy hour are used to calculate the traffic load, capacity of the mobile communication network equipment and to determine traffic performance indicators. Data was obtained from OMC for a period of a year. The OMC is in-built within the mobile communication network, that help to monitor and measure all the entire event in the mobile communication system. The obtained data was analyzed using excel package to determine the busy hour which was observed to be 19:00 (7.00pm) shown in figure 2.1 to figure2.6 the call intensity for various days of the week is as followed, Monday with the highest call intensity, 26,492, followed by Friday with 23,138, Tuesday with 19,080, Wednesday with 17,892, Thursday with 16,467, Saturday with 15,491 and Sunday with 12,119.